STRATEGI PENGEMBANGAN WILAYAH MELALUI PEMETAAN DAYA SAING EKONOMI KAWASAN KARESIDENAN PEKALONGAN - Karunia, Anita; Faidah, Yusri Anis (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2017)
This research aims to find regional potential in the area of Pekalongan Eks Residency through comparative advantage, competitive advantage, and specialized analysis therefore can be arranged the regional development strategy. This research is analyzed using quantitative descriptive method with the analysis of Static Location Quotient (SLQ) and Shift Share (SS) with the modification of Estaban Marquiles. The result of this research shows that the result of SLQ analysis shows sector with comparative advantage in all regency/city of Pekalongan Eks Residency is the sector of Accommodation, Food and Beverage Provision. Sectors that can be comparative advantage potential in all regency/city in Pekalongan residency are the Sectors of retail trade, car and motor bike repairs; Education service sector; and Other services sectors. The result analysis of Esteban Marquiles Shift Share shows that several sectors have competitive advantage in each regency/city in Pekalongan residency although not as whole such as Mining and Digging Sector exceptÂ  Pekalongan City and Tegal City; Processing industry sector except Batang Regency; and also Company services sector except Tegal Regency and Pekalongan City. The difference of result of sectoral potential analysis of Regency/city in Pekalongan residency becomes the foundation in arranging regional development strategy surgically that is by looking into what sector/commodity that can be developed rapidly, either because of the nature potential or because that sector has competitive and comparative advantage to be developed.